2015
DOI: 10.1007/s11105-015-0948-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IPT in Asakura-sanshoo (Zanthoxylum piperitum (L.) DC. f. inerme Makino) Alters Tree Architecture, Delays Leaf Senescence, and Changes Leaf Essential Oil Composition

Abstract: The IPT gene encodes isopentenyl pyrophosphate transferase, a key enzyme in cytokinin biosynthesis. We introduced IPT under the control of the CaMV35S promoter into Asakura-sanshoo (Zanthoxylum piperitum (L.) DC. f. inerme Makino) via stable Agrobacterium tumefaciens-mediated transformation. Three of 3-year-old transgenic Asakura-sanshoo lines Y5, Y16, and Y17 were used to evaluate the effects of IPT expression on the morphological characteristics, leaf senescence, and essential oil composition. Introduced IPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…This is correlated with the general decrease in cytokinin content observed during leaf senescence in N. tabacum while an increase in the endogenous cytokinin level leads to a delay in senescence processes (Yu et al, 2009). Our results are also in agreement with the fact that over-expression of the isopentenyltransferase gene, responsible for cytokinin biosynthesis, generally leads to senescence delay and stay-green phenotypes in numerous species including B. napus (Kant et al, 2015; Zeng and Zhao, 2016). Because ABA, SA and cytokinins seem to be strongly involved in the regulation of leaf senescence in B. napus L., we focused our analysis on the content of these phytohormones.…”
Section: Resultssupporting
confidence: 90%
“…This is correlated with the general decrease in cytokinin content observed during leaf senescence in N. tabacum while an increase in the endogenous cytokinin level leads to a delay in senescence processes (Yu et al, 2009). Our results are also in agreement with the fact that over-expression of the isopentenyltransferase gene, responsible for cytokinin biosynthesis, generally leads to senescence delay and stay-green phenotypes in numerous species including B. napus (Kant et al, 2015; Zeng and Zhao, 2016). Because ABA, SA and cytokinins seem to be strongly involved in the regulation of leaf senescence in B. napus L., we focused our analysis on the content of these phytohormones.…”
Section: Resultssupporting
confidence: 90%
“…[ 4 , 6 ]. Isopentenyltransferase (IPT) catalyzes the first and rate-limiting step of CTK biosynthesis [ 7 , 8 ]. The isopentenyladenine (iP)-type CTKs biosynthesized in the stem node of tomato ( Solanum lycopersicum ) promote axillary bud sprouting and lateral branch growth [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cook et al [ 10 ] reported that the upregulated expression of A-IPT in axillary buds and stem nodes stimulates the outgrowth of axillary buds. Overexpression of the A-IPT gene in Asakurasanshoo [ 7 ], Chrysanthemum [ 1 , 8 ] and Arabidopsis [ 8 ] resulted in increased branching.…”
Section: Introductionmentioning
confidence: 99%
“…These pathways play a role at all stages of senescence, whether they be the initiation, progression, or final stage of senescence [ 18 , 19 , 20 , 21 , 22 , 23 ]. Cytokinins (CKs), gibberellins (GAs), and auxin (IAA) are hormones involved in the negative regulation of senescence [ 20 , 24 , 25 , 26 , 27 ]. In contrast, abscisic acid (ABA), salicylic acid (SA), ethylene (ET), methyl jasmonate (MeJA), brassinosteroids (BR), and strigolactones (SL) have the capacity to positively regulate senescence [ 18 , 19 , 20 , 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%